Development of Wave Material Worksheets Based on Science Process Skills - Haq, Nur Izzati; Amri, Tasdik Husni (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
The aim of this research is to develop a worksheet based on science process skills on wave material and determine student perceptions of the worksheet developed. This type of research is development research with a 4D development model including define, design, develop and disseminate stages. The test subjects for this research were physics education students who took basic physics II courses. The instruments used were expert validation questionnaires and student perception questionnaires. Data analysis techniques in the form of validation questionnaire scores and student perception questionnaires were carried out using descriptive statistics. Meanwhile, data analysis resulting from document review during initial observations and validator suggestions was carried out in a qualitative descriptive manner. The result of this research is a worksheet based on science process skills on wave material. The specifications contained in this worksheet are that the worksheet is designed with an attractive cover appearance and is equipped with appropriate images. The reliability of the student perception questionnaire is in the good category. Results of analysis of student perceptions on aspects of worksheet cover design, worksheet content design, presentation components, Science Process Skills aspects and linguistic components. From these four aspects, it was found that the results of students' perceptions of the Worksheet Based on Science Process Skills in Wave Material were very good.